PENGARUH KERAMAHAN DAN PENGETAHUAN PRODUK BEAUTY ADVISOR TERHADAP PENINGKATAN PENJUALAN POND’S DI CV. BIN WAHAB GROUP SUGIO LAMONGAN - Nafahatus Sahariyah; Siti Shoimah (LPPM UNISDA, 2020)
This research was conducted at CV. Bin Wahab Group. This study aims to determine whether there is an influence or not from the hospitality and knowledge of beauty advisor products to increase sales of pond’s both simultaneously and partially. The background of this study, the researcher chose the variable because the friendliness to the consumer variable will increase consumer confidence in the beauty advisor in explaining product knowledge that can be directed to the product being sold so as to increase sales. This research uses quantitative methods. Primary collection techniques were obtained from observations and questionnaires, while secondary data were obtained from literature studies. In determining data collection obtained from respondents through a simple random sample. The method of data analysis uses statistical tests that are operated through the SPSS 25 program. The results of partial or simultaneous test of hospitality variables and product knowledge have a positive effect on sales increase. Product knowledge has a higher influence that is if it rises by one unit, it will be followed by an increase in sales of 0.545 units compared to hospitality.